Synthesis: climate effects on biodiversity, abundance and distribution of marine organisms in the Benguela. (March 2015) - Jarre, Astrid; Hutchings, Laurence; Kirkman, Stephen P.; Kreiner, Anja; Tchipalanga, Pedro C.M.; Kainge, Paulus; Uanivi, Uatjavi; van der Plas, Anja K.; Blamey, Laura K.; Coetzee, Janet C.; Lamont, Tarron; Samaai, Toufiek; et al.
Abstract: The NansClim project (2010–2013) represented a regional collaboration to assess the effects of climate on Benguela dynamics. Based on in situ (since the 1960s in Namibia and South Africa and 1985 in Angola) and satellite (since the 1980s) observations, the project focussed on four subsystems, namely the Angola subtropical, northern Benguela upwelling, southern Benguela upwelling and Agulhas Bank. This contribution summarizes the findings for selected key questions, ranging from changes in the physico‐chemical habitats, plankton, pelagic and demersal fish communities, to cross‐cutting evaluation at subsystem and regional scales. The results underline the overriding importance to of considering the combined effects of climate and fishing as drivers of the dynamics of the ecosystem components. Each subsystem currently continues to function largely as a separate entity as described in earlier reviews. However, some changes have been observed across several subsystems, e.g., a coherent shift from one relatively stable period to another occurred in the northern and southern Benguela in the mid‐1990s. Future climate change could weaken the boundaries between the four subystems. The findings underline the need for continued regional research collaboration and regional surveys focussed at ecosystem, rather than resource, assessment. Our conclusions include implications for ecosystem‐based fisheries management, and recommendations for future regional research.